66‐4: Invited Paper: Graphene Enhanced QD Image Sensor Technology. Issue 1 (28th June 2021) - Allen, Mark; Bessonov, Alexander; Ryhänen, Tapani
Abstract : Machine vision is a driver for novel imaging solutions covering wavelength range from visible to SWIR light. Emberion produces high‐performance industrial cameras based on its own monolithically CMOS integrated image sensors that are built on two unique innovations: 1) using a combination of colloidal quantum dots and graphene, and 2) optimising the measurement principles and ROICs according to the requirements of these nanomaterials. Characteristics and performance of our photodetector structures, image sensors and cameras are discussed, highlighting the benefits of graphene electronics. Our devices have photoresponse from 400 nm to 2100 nm, with low noise at high frame rates.